Maintaining Family Collection Through Ruqyah Syar'iyah : Maqashid Syari'ah Perspective - Fahmida, Nurul; Irham, M. Iqbal (Dinasti Research, 2024)
This article discusses maintaining family integrity through Ruqyah Syar'iyah from the perspective of Maqashid Syari'ah at the Ruqyah Syar'iyah Institute in Aceh. The importance of writing this article is based on the complexity of the challenges faced by modern families, including the threat of tafriq magic to house hold harmony. The purpose of this article is to explore the concept of Ruqyah Syar'iyah and analyze its contribution in maintaining family integrity. This research uses a field approach with a case study at the Aceh Ruqyah Syar'iyah Institute, involving observation, interviews, and literature study. The results of the discussion include an in-depth understanding of Ruqyah Syar'iyah as a form of Islamic medicine and the urgency of applying Maqashid Shari'ah in maintaining the family. The conclusion of this article is that understanding the concept of Ruqyah Syar'iyah and the application of Maqashid Syari'ah are important foundations in maintaining family integrity, creating an atmosphere of rabbaniyah, and maintaining the noble purpose of marriage as part of Islamic preaching.